Are stock and housing returns complements or substitutes? Evidence from OECD countries - Guglielmo Maria Caporale; Ricardo M. Souza (Deutsches Institut für Wirtschaftsforschung (DIW), 2011)
In this paper we use a representative consumer model to analyse the equilibrium relation between the transitory deviations from the common trend among consumption, aggregate wealth, and labour income, cay, and focus on the implications for both stock returns and housing returns. The evidence based on data for 15 OECD countries shows that when agents expect future stock returns to be higher, they will temporarily allow consumption to rise. Regarding housing returns, if housing assets are seen as complements to stocks, then investors react in the same way, but if they are instead treated as substitutes consumption will be temporarily reduced.
Keywords: E21; E44; D12; 330; consumption; wealth; stock returns; housing returns; OECD countries